Aneurisms of gastro-duodenal and pancreatic-duodenal arteries: Surgical procedures - Siano Quirós, Ruben; D'Angelo, Mario; Pardo Berbel, Domingo (Cirugía del Uruguay, 1984)
Authors present three cases of patients with aneurisms of the gastroduodenal and pancreatic-duodenal arteries. Some considerations are provided concerning the techniques available to the surgeon for the treatment of this affection.